Sensitive Optical Authentication of Honey: Probing 5% Adulteration with Laser‑Induced Speckle Textures - Patel, Hemraj Bhai; Kumar, Atul; Nirala, Anil Kumar (Photonics Letters of Poland, 2025)
This study employs the Dynamic Laser Speckle Technique (DLST) with grey-level co‑occurrence‑matrix analysis to detect 5 % burra‑sugar adulteration across eight commercial honeys. A spatially filtered He–Ne laser beam interacted with liquid samples, producing speckle images captured at 64 fps by a CMOS sensor. Seven statistical textural metrics were extracted from the speckle images using MATLAB software. Average absolute percentage change in metrics such as cluster prominence, variance, and contrast changes by 12.4 %, 6.2 %, and 5.5 % respectively. The average change in inertia moment (IM) and absolute value difference (AVD) are -7.64 % and -5.39 %, respectively. DLST costs < 1 per sample, offering an economical safeguard for honey quality.